Using POSSE Strategy in Teaching Reading Comprehension - Sudarkam R. Mertosono; Erniwati Erniwati; Hastini Hastini; Muhammad Arid (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
This research aims to determine if using POSSE Strategy affects reading comprehension of students majoring in English education of Tadulako University. This is a pre-experimental study using the one group pretest and posttest design. The population was 319 students in academic year 2018/2019. The samples were 35 students selected employing purposive sampling technique. Paper-and-pencil method was used when collecting the data with a test as the instrument. The test was administered twice namely pretest and posttest. The data were analyzed statistically using .05 level of significance and 34 degree of freedom. The result showed that after receiving intervention through POSSE Strategy, students scores got improved. In other words, using POSSE Strategy is effective in improving the sampled-students’ reading comprehension on any kinds of English text.